Bronchiolitis obliterans syndrome leads to a functional deterioration of the acinus post lung transplant. Issue 5 (8th November 2013) - Thompson, Bruce R; Hodgson, Yvonne M; Kotsimbos, Tom; Liakakos, Pam; Ellis, Matthew J; Snell, Gregory I; Verbanck, Sylvia
Abstract : ABSTRACT: Bronchiolitis obliterans syndrome (BOS) limits long-term survival of lung transplant recipients, and airflow obstruction in these patients likely originates in the small airways. 61 double lung transplant recipients performed multiple breath nitrogen washouts to obtain indices of acinar and conductive ventilation heterogeneity (Sacin, Scond ). There was a significant association of BOS status with Sacin (Kruskal–Wallis; p<0.001) but not with Scond (p=0.1). These results demonstrate that it is the structural alteration of the terminal bronchioles, generating ventilation heterogeneity at the level of the diffusion front, and not the bronchioles located more proximally, that is driving the airflow obstruction that determines BOS status.